The role of estuarine wetland in carbon storage for climate change mitigation: A bibliometric analysis - Fajeriadi Hery; Fahmi Fahmi; Dharmono Dharmono; Zaini Muhammad; Putra Aminuddin Prahatama; Suyidno Suyidno; Irhasyuarna Yudha; Suryajaya Suryajaya; Saifuddin Much. Fuad (BIO Web of Conferences)
The 2023 progress report on the Sustainable Development Goals (SDGs) is weak, even regressing, including key targets related to climate change, and at risk of failure. Estuarine ecosystems dominated by mangrove vegetation are critical for climate change mitigation. However, these ecosystems continue to be degraded at multiple levels. Indonesia, with the largest mangrove forest area in the world, requires conservation and restoration efforts to effectively mitigate climate change impacts. This study aims to analyze the role of estuarine ecosystems in storing carbon for climate change mitigation. This research uses bibliometric analysis method to produce an in-depth and comprehensive analysis. The data source is the Scopus database, visualized using the VOSviewer application. After limitation, 219 out of 1485 documents that fit the inclusion criteria were obtained. The results showed a significant increase in interest in the topic of the role of estuarine ecosystems for climate change mitigation in the last two years. This research underscores the importance of mangroves restoration in estuarine ecosystems, as their condition has significant impacts on climate change and coastal communities. Nature-based solutions such as the use of green energy, implementation of new technologies such as remote monitoring, and ecosystem balance-based policy-making are recommended. The integration of multi-disciplinary and multi-technology approaches is crucial to build resilient, natural estuarine ecosystems and restore ecosystem services. These findings can also provide a scientific basis for the management of estuarine ecosystems to support SDG 13 Climate Action.